متطلبات اعتماد السياسة النقدية المثلى حالة الجزائر2003-2019 - زناقي, سيداحمد; برزين, ايوب (جامعة الوادي University of Eloued, 2020)
This study aimed to find out whether the DSGE model is stable in the long term and the interest rates announced by the Central Bank of Algeria are in line with the mechanisms of the Taylor rule in the period between 2003 and 2019, by applying the recognized statistical tools based on the method of the autoregressive model. This study concluded that the DSGE model is not stable and that the reactions of monetary policy in Algeria do not comply with the application of Taylor's rule of rational expectations due to the absence of a basic production base far from the prices of fuels and this is based on the results shown in the study According to the effect of inflation.
The requirements for adopting an optimal monetary policy, the case of Algeria 2003-2019
مقال
Keywords: نموذج DSGE ; التضخم ; قاعدة تايلور للتوقعات العقلانية ; البنك المركزي الجزائري